Secure love eaudiobook Create a relationship that lasts a lifetime. - Menanno, Julie (Simon & Schuster Audio, 2024)
Create a lasting and loving attachment with this national bestseller, a "must-read for every couple, at any stage of their relationship" (Lori Gottlieb, New York Times bestselling author of Maybe You Should Talk to Someone ) from the expert couple's therapist behind the popular Instagram account @TheSecureRelationship. What does a healthy relationship look like? A good question, in theory, but couple's therapist Julie Menanno wants you to consider: what does a securely attached relationship feel like? The answer to this question is the ultimate goal in Secure Love , an "incredibly wise and helpful guide" (Jen Sincero, New York Times bestselling author of You Are a Badass ) to understanding secure attachment in adult relationships. While attachment theory has grown in popularity to explain the relationship between children and their caregivers, it's also the closest science has come to making sense of our adult romantic connections. In this book Julie Menanno, the expert behind the popular Instagram account @TheSecureRelationship, tackles: -Why you and your partner have the same fight over and over (hint: it's called a negative cycle, and underlying every fight, argument, silent treatment, or passive-aggressive comment is an unmet attachment need). -"Instead of that, say this" suggested scripts of how to approach difficult situations in your relationship more effectively. -The four attachment types, with exercises to understand you and your partner's attachment style. -How to improve communication, including staying connected during conflict by prioritizing vulnerability rather than protecting yourself. -Why insecure attachment negatively impacts a couple's sex life and how to ignite that sexual connection. Secure Love is a crash course in understanding how you show up in a relationship and guides you on getting out of negative cycles to find safety in one another. In doing so, "you'll be armed with eternal wisdom for strengthening your relationship" (Dr. Sue Johnson, founder of Emotionally Focused Therapy for Couples and bestselling author of Hold Me Tight ) and establish a secure attachment with your partner to create the bond you've been longing for.